Long-term outcome of conservative and invasive treatment in patients with hypertrophic obstructive cardiomyopathy. Issue 3 (4th May 2019) - Hoedemakers, Sarah; Vandenberk, Bert; Liebregts, Max; Bringmans, Tijs; Vriesendorp, Pieter; Willems, Rik; Van Cleemput, Johan
Abstract: Background and objective: Treatment for patients with hypertrophic obstructive cardiomyopathy (HOCM) can be either conservative or invasive (alcohol septal ablation (ASA) and myectomy). As there is no clear consensus on the long-term effects of these different strategies, the aim was to compare the long-term outcome in a large tertiary referral university hospital. Methods: We retrospectively included 106 HOCM patients. Twenty-nine (27.4%) patients were treated conservatively, 25 (23.6%) underwent ASA and 52 (49.0%) myectomy. Endpoints were all-cause mortality and sudden cardiac death (SCD)-related events (including SCD, aborted SCD and appropriate ICD shocks). Kaplan–Meier survival analysis and Cox proportional hazard regression models were used. Results: The mean follow-up period was 7.7 ± 4.9 years. Overall, there was no significant difference in survival between the three treatment strategies ( p = 0.7). Annual rates of SCD-related events at 5 years and the complete follow-up period were significantly higher ( p = 0.034) after conservative treatment (4.9%/year and 2.7%/year, respectively) compared to ASA (0.9%/year, 0.5%/year) and myectomy (1.0%/year, 0.6%/year). Independent predictors of SCD-related events were: conservative treatment (HR 10.66; 1.88–60.55), a known mutation (HR 9.36; 1.43–61.20), left ventricular wall thickness (LVWT) > 30 mm (HR 6.48; 1.05–39.92) and non-sustained VT (HR 16.82; 2.29–123.29). Invasive treatment resulted in a significant higher proportion of patients requiring pacing ( p = 0.033). Conclusions: Long-term mortality rates for patients with HOCM are similarly low between treatment groups. However, conservative treatment was associated with SCD-related events, as were known mutations, increased LVWT and non-sustained VT. Invasive treatment was associated with a higher need for implantation of a pacemaker.